Computer vision syndrome among Al-Rayan Medical Colleges students, Madinah, Saudi Arabia - Elhassani, Abdallah; Aljohani, Rahaf; Eisawi, Khawlah; Alsaedi, Ghadi; Alhilali, Maysa; Watad, Bushra; Jeha, Bana; Alharbi, Arwa; Mohammed, Nesreen; Alkurdi, Abdullah A. (International Journal of Research in Medical Sciences, 2023)
Background: Digital devices now become a part of university student’s life, and with prolonged use, they may experience some ocular problems like dryness, headache, eye strain, and pain. These symptoms and others constitute computer vision syndrome (CVS). Our study aimed to assess CVS among Al-Rayan medical college students and to evaluate students’ behaviors related to preventing CVS. Methods: A cross-sectional, questionnaire-based study was performed among the students of Alrayan Medical College from the period from November to December 2022, with a sample size of 270 cases. Data were collected using (CVS-Q) questionnaire. Results: Near half of the participants (53.7%) were suffering from CVS. The most reported symptoms included headache (43.3%), tearing (42.9%), burning (39.3%), and blurred vision (35.1%). The most significant measures applied to minimize the impact of electronic devices were putting the digital device at enough distance (p value=0.001) and adjusting the screen brightness of the digital device (p value=0.004). Conclusions: This study disclosed that CVS is a common problem among medical students. The manifestation of CVS was affected by the frequency and duration of electronic device use.